Traumatic brain injury and autophagy: a pilot study about the immunohistochemical expression of LC3B, Beclin 1, p62, and LAMP2A in human autoptic samples - Livieri, Tommaso; Alfieri, Letizia; Giacomello, Emiliana; Alempijević, Djordje; Petrovic, Tijana; Kolev, Yanko Georgiev; Radaelli, Davide; Neri, Margherita; D’Errico, Stefano (Frontiers in molecular neuroscience, 2025)
Autophagy is a cellular stress response that has been shown in the literature to be active in cerebral cells after a traumatic brain injury (TBI). The aim of this study is to investigate the potential use of four proteins involved in autophagy (LC3B, Beclin 1, p62, and LAMP2A), as a forensic diagnostic marker for TBI. We analyzed histological samples obtained from the frontal lobe of 10 subjects who died within 1 h of a TBI (Group A), 13 who died between 1 h and 32 days post-TBI (Group B), and a control group of 10 subjects who died without head trauma (Group C). Immunohistochemical (IHC) staining using anti-LC3B, anti-Beclin 1, anti-p62 and anti-LAMP2A antibodies was performed. The results show that LC3B staining was the only one that show a statistically significant difference between groups. In particular, the percentage of neurons displaying an autophagic pattern was calculated from six random acquisitions per subject, and the results were compared across groups using one way ANOVA. Significant differences were observed between Groups A and B, and between Groups B and C, with -values of 0.0055 and 0.0035, respectively. While the difference between Groups A and C was not statistically significant ( -value of 0.9845). These findings suggest that LC3B may serve as a useful diagnostic marker for TBI in cases where death is not immediate and open the door for further research.